2011
DOI: 10.2174/1874839201105010013
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Seal Habitat Use of Nearshore Waters around Newfoundland and Southern Labrador: Implications for Potential Predation on Salmon

Abstract: Abstract:The reasons for the decline in some Atlantic salmon (Salmo salar) stocks in Newfoundland and southern Labrador are not fully understood, but many resource users consider predation by seals in rivers and nearshore waters to be a contributing factor. To address these concerns, local ecological knowledge (LEK) interviews with resource users (n = 57) were conducted at 29 rivers throughout the Province to evaluate the potential for seal predation over a 25-year period when major changes were occurring in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Additionally, a further 11 species (37% of all prey items) were identified through other skeletal structures alone, including salmonids. While grey seal predation on north Atlantic salmonids has been documented (Lenky & Sjare 2011), there is little evidence from dietary studies to support these observations. For example, studies in the northeast of Scotland have found very little evidence of salmonids in the diet (McConnell et al 1984, Prime & Hammond 1985.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a further 11 species (37% of all prey items) were identified through other skeletal structures alone, including salmonids. While grey seal predation on north Atlantic salmonids has been documented (Lenky & Sjare 2011), there is little evidence from dietary studies to support these observations. For example, studies in the northeast of Scotland have found very little evidence of salmonids in the diet (McConnell et al 1984, Prime & Hammond 1985.…”
Section: Discussionmentioning
confidence: 99%